Which strategies can an educational business, such as a kindergarten in Germany, develop to foster employee engagement? - Picq, Caroline (2016)
Which strategies can an educational business, such as a Kindergarten in Germany, develop to foster employee engagement? The goal of this master thesis is to identify effective and viable measures to engage employees, that could be potentially implemented in a Kindergarten in Germany. The literature concerning the notion of employee engagement is so inconsistent that even studies about the subject fail to find one common definition and have to acknowledge the variety of existing definitions (IES, 2014, p.52-53). This reflects the youth of the concept, which has only been partially studied by academics and practitioners in recent years. The literature gap about employee engagement concerns many aspects, among which small companies and educational businesses, in particular those focusing on early child development. Considering the low levels of employee engagement in Germany combined with the absence of studies on educational organizations focusing in early child development this master thesis studies engagement in German Kindergärten(s). This master thesis is divided in two parts consisting of a literature review and a case study. The literature review allows to follow the evolution of the concept along the years, while the case study focuses on assessing employee engagement in Montessori Kindergärten(s) in Munich & elaborating potential measures to increase engagement levels. Double sided research was undertaken for this case study. On the one hand a quantitative research was performed, through a survey, in order to uncover which strategies would be viable to foster employee engagement. On the other hand a qualitative research was undertaken, consisting in an internship in a Kindergarten, in order to shed light on how to do so. Findings in the quantitative research indicate overall engagement levels average to low. Results related to specific statements bring out the originality of the educational sector, which is in some aspects intrinsically engaging, similarly to the medical field (Seijts & Crim, 2006). Furthermore low engagement levels led to a conversely high number of positives responses to potential engagement strategies suggesting their potential effectiveness. Findings in the qualitative research are coherent with qualitative results and complement them